Great Powers' Doctrine in the Information Warfare (Journal of the Spanish Institute for Strategic Studies, 2024)
Information Warfare is a type of conflict that transcends the traditional realm of armed confrontation. The struggle within the information domain has persisted throughout human history, evolving with every advancement in information management technologies, from parchment to the internet. Through a comparative analysis, this paper focuses on the doctrinal vision and approach of the three current major powers: the United States, China, and Russia. Given their advanced media and technological capabilities, these powers emerge as dominant protagonists in this informational confrontation arena. Similarly, their status in the international system, from which a vast array of opposing interests arises, places them in a perpetually latent conflict scenario. Hence, they provide the most substantial base of examples and resources for the study of this phenomenon. By examining their recent history, as well as their doctrinal documents and primary academic contributions, we come to understand not only their strategies and tactics but also the dynamics of competition and the evolution of Information Warfare in the contemporary context.
Keywords: Cognitive Warfare, Cyber Warfare, Propaganda, Realism, Foreign Policy.